2011
DOI: 10.1016/j.pep.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human sperm-specific glyceraldehyde-3-phosphate dehydrogenase (GAPDHS) is expressed at high yield as an active homotetramer in baculovirus-infected insect cells

Abstract: The sperm-specific glyceraldehyde-3-phosphate dehydrogenase (GAPDHS) isoform is a promising contraceptive target because it is specific to male germ cells, essential for sperm motility and male fertility, and well suited to pharmacological inhibition. However, GAPDHS is difficult to isolate from native sources and recombinant expression frequently results in high production of insoluble enzyme. We chose to use the Bac-to-Bac baculovirus-insect cell system to express a His-tagged form of human GAPDHS (Hu his-GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Expression of full-length GAPDHS in E. coli has proven difficult in quantities sufficient for screening a large number of compounds [ 7 ]. Substantially better yields and activities were obtained by elimination of the proline-rich N-terminal region [ 1 ] that is not required for enzyme activity [ 22 ]. When typical E. coli strains were used for expression, mass spectrometry analyses confirmed that mouse GAPDHS and the host bacterial GAPDH formed mixed tetramers, resulting in the co-purification of bacterial and recombinant enzymes (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of full-length GAPDHS in E. coli has proven difficult in quantities sufficient for screening a large number of compounds [ 7 ]. Substantially better yields and activities were obtained by elimination of the proline-rich N-terminal region [ 1 ] that is not required for enzyme activity [ 22 ]. When typical E. coli strains were used for expression, mass spectrometry analyses confirmed that mouse GAPDHS and the host bacterial GAPDH formed mixed tetramers, resulting in the co-purification of bacterial and recombinant enzymes (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Typical yields were ~13 mg of purified GST-GAPDHS per 6L E. coli culture. Hu GST-GAPDHS protein purified from E. coli was further characterized by analytical size exclusion chromatography as previously described [ 22 ]. GST-GAPDHS was applied to a Superose 12 column and eluted as a mixture of three forms (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This proline-rich part confers a change in biochemical properties of the enzyme. While GAPDH is an abundant cytoplasmic protein, highly soluble and easy to purify and crystallize, the sperm GAPDHS protein becomes highly insoluble, slowly migrating in the gel, and numerous attempts to determine the crystal structure of the whole protein failed due to its properties [ 9 - 11 ]. Its crystal structure without the N-terminal part was found and shows high similarity to the somatic enzyme.…”
Section: Introductionmentioning
confidence: 99%